2019
DOI: 10.2147/ndt.s188111
|View full text |Cite
|
Sign up to set email alerts
|

<p>A meta-analysis of levetiracetam for randomized placebo-controlled trials in patients with refractory epilepsy</p>

Abstract: Objective The objective of this study was to investigate the efficacy and safety profile of levetiracetam as add-on therapy in patients with refractory epilepsy. Methods Web of Science, MEDLINE (Ovid and PubMed), Cochrane Library, EMBASE, and Google Scholar were systematically searched to identify potential eligible randomized controlled trials by two reviewers independently. Pooled estimates of risk ratios (RRs) for 50%, 75%, and 100% reduction from baseline were calcu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 34 publications
0
15
0
1
Order By: Relevance
“…There was a 75% reduction in seizures through using LEV, with similar results for doses of 2,000 and 3,000 mg. The safety of LEV was comparable to that of placebo 7 .…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…There was a 75% reduction in seizures through using LEV, with similar results for doses of 2,000 and 3,000 mg. The safety of LEV was comparable to that of placebo 7 .…”
Section: Discussionmentioning
confidence: 80%
“…It is recommended as a first-line add-on agent for focal seizures and, additionally, has a favorable pharmacokinetic profile. Studies have shown that LEV is an effective anti-seizure medication for both adults and children with generalized or focal-onset refractory seizures, at doses of 1,000-3,000 mg/day or 60 mg/kg/day, with an acceptable adverse event profile 7 . However, little information about LEV use in the Brazilian population is available.…”
Section: Introductionmentioning
confidence: 99%
“…Humans have higher levels of SV2A in the amygdala than in other tissues, based on genome-wide expression profiling data 61,62 . SV2A is the binding site of the anticonvulsant drug levetiracetam ((S)-α-Ethyl-2-oxo-1-pyrrolidineacetamide) 52 , which has shown promise in anxiety disorder treatment [63][64][65][66][67][68][69] , but also generates states of anxiety as a side-effect in some individuals 70,71 . Such individual differences may reflect underlying genetic variations, which is very plausible, given that multiple SV2A SNPs are associated with anxiety by GWAS.…”
Section: Discussionmentioning
confidence: 99%
“…6 Levetiracetam is the most widely used antiepileptic drug in the United States, in large part because of its efficacy and generally favorable safety profile. 11 A recent meta-analysis by Cao et al 12 showed a positive response, with greater than 50% reduction in seizure or seizure freedom in children who use levetiracetam as adjunctive therapy for focal epilepsy compared to placebo. However, a Cochrane Review by Mbizvo et al 10 found the rate of behavioral side effects in children treated with levetiracetam to be as high as 23%.…”
Section: Discussionmentioning
confidence: 99%